Perbandingan Reduksi Glukosa Pada Urin Menggunakan Pemanasan Api Spirtus Dan Waterbath 100oC Dengan Metode Benedict - Anita Kurniyawati; Fitri Fadhilah; Anggi Nopiani (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2019)
The high prevalence of DM is a global problem that must be handled by health workers around the world. The number of DM patients in the world in all age groups was 382 million people in 2013 and is estimated to increase 55% to 592 million sufferers in 2035. In Indonesia, provinces with the highest prevalence of DM are D.I. Yogyakarta with 2.6%, both Jakarta 2.5%, and third North Sulawesi with 2.4%. The prevalence of DM in South Kalimantan was ranked 13th at 1.4%. This study aims to determine the differences in the results of urine reduction examination benedict method using spirtus flame with waterbath 100° C. This research method is a laboratory experiment. The results of this study indicate that the urine reduction examination by heating flame flame and waterbath 100oC shows the same results from negative (-) until positive (+4). Examination of urine reduction by heating the flame of spirits and waterbath 100oC does not affect the results. But there is a difference in the process with heating flame methylate a longer time is 3-5 minutes, when boiling the solution in the tube explodes and can only work one by one sample, while the heating of 100oC waterbath the time required is relatively faster, 2 minutes, not explode when boiling, and can work 6-8 samples (depending on the tube rack you have). If the number of patients is much better the urine reduction examination benedict method uses a 100oC waterbath heating.